Testamenta cantiana: A series of extracts from fifteenth and sixteenth century wills relating to church building and topography. West Kent (Hughes and Clarke, 1906)
With ills and index. With: Arthur Hussey, Testamenta cantiana: A series of extracts from fifteenth and sixteenth century wills relating to church building and topography. East Kent.